Administrative styles in the OECD: bureaucratic policy-making beyond formal rules - Enkler, Jan et al (2017)
As we know from comparative public policy, bureaucracies contribute to a considerable degree to the contents and the ways of policy-making. One important driver of administrative policy-making are their specific "styles" or "cultures". "Administrative styles" are understood here as the standard operating procedures and routines that characterize the behavior and activities of administrative bodies in initiating, drafting and implementing policy. In this article, we convey the concept of Administrative Styles to the level of International Organizations (IOs) and apply it to the Organization for Economic Development and Co-Operation (OECD). The article proceeds in three steps: First, the concept of administrative styles is introduced and refined. Drawing on expert interviews with OECD staff, we secondly show that consideration of OECD administrative styles significantly advances the literature's understanding of the organization. Finally, we give an outlook on new research avenues and the relevance of our findings for the study of International Public Administrations (IPAs) more generally. - Reproduced.
Keywords: Public administration; Policy making; Bureaucracy